Setting the Scene: Livestock Production and Feed Resources in Ethiopia - Assefa, Getnet (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in Media Training Workshop on Climate Smart Feed and Forage Innovations. Addis Ababa, Ethiopia.